Roquea, a new genus of Lychnophorinae (Vernonieae, Asteraceae) from Brazil and its phylogenetic placement - Loeuille, Benoît; Almeida, Roberto Baptista Pereira; Siniscalchi, Carolina M.; Lusa, Makeli G.; Antar, Guilherme Medeiros (Phytotaxa, 2024)
Lychnophorinae (Vernonieae, Asteraceae) consists of 21 genera and approximately 150 species, primarily distributed in the Brazilian Central Plateau, with several novelties recently described. With new botanical expeditions conducted in Serra da Formosa, state of Minas Gerais, a set of collections that belong to Lychnophorinae but were not easily assigned to a genus was discovered. After morphological and anatomical analyses and phylogenetic studies, we describe and illustrate Roquea, a new genus of Asteraceae from Brazil, to accommodate the new species Roquea multiserialis. Affinities of the new genus with other genera of Lychnophorinae are discussed along with a preliminary conservation status assessment, and notes on its distribution, ecology and affinities. This new finding contributes to the understanding of the taxonomy and evolution of Lychnophorinae and the campos rupestres and supports the urgent need to preserve Serra da Formosa, currently threatened by human activity.